EXPERIMENTAL STUDY ON THE FLOW REGIME IDENTIFICATION IN THE CASE OF CO-CURRENT CONDENSATION OF R134a IN A VERTICAL SMOOTH TUBE - Dalkilic, Ahmet Selim; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2010)
The present study investigates an intensive comparison of flow regime maps for the verification of annular condensation flow of R134a checked by sight glasses at the inlet and outlet sections of a vertical smooth copper tube having inner diameter of 8.1 mm and a length of 500 mm. R134a and water are used as working fluids in the tube side and annular side of a double tube heat exchanger, respectively. The experimental apparatus are designed to capable of changing the different operating parameters such as mass flow rate, condensation temperature of refrigerant, cooling water temperature and mass flow rate of cooling water etc. and investigate their effect on heat transfer coefficients and pressure drops. Condensation experiments are performed at the mass flux of 456 kg m(-2)s(-1), the saturation temperature is around 40 degrees C, heat fluxes and average qualities are between 16.16- 50.89 kW m(-2) and 0.81-0.93 respectively. Considering Chen et al.'s annular flow theory on the heat transfer coefficients that are independent from tube orientation as long as annular flow exists along the tube length, experimental data belong to annular flow inside the test tube are plotted on the various flow regime maps and used in the flow regime identification correlations proposed for two-phase flow in horizontal and vertical tubes separately. In spite of their different operating conditions, Barnea et al., Hewitt and Robertson, Baker, Thome, Kattan et al., Chen et al.'s flow regime maps and Taitel and Dukler's, Dobson's, Akbar et al.'s, Breber et al.'s, Cavallini et al.'s, Soliman's flow pattern correlations from literature are found to be predictive for the annular flow conditions in the test tube.
Keywords: HEAT-TRANSFER COEFFICIENT; 2-PHASE FRICTION FACTOR; VOID FRACTION MODELS; HIGH-MASS FLUX; DOWNWARD FLOW; PATTERN TRANSITION; HORIZONTAL TUBES; PART 1; DIAMETER; Thermodynamics; Engineering